2021
DOI: 10.3390/ijms22063162
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-Gallate Protects Pro-Acinar Epithelia Against Salivary Gland Radiation Injury

Abstract: Antioxidant agents are promising pharmaceuticals to prevent salivary gland (SG) epithelial injury from radiotherapy and their associated irreversible dry mouth symptoms. Epigallocatechin-3-gallate (EGCG) is a well-known antioxidant that can exert growth or inhibitory biological effects in normal or pathological tissues leading to disease prevention. The effects of EGCG in the various SG epithelial compartments are poorly understood during homeostasis and upon radiation (IR) injury. This study aims to: (1) dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…SG pretreated with 7.5 µg/mL of EGCG promoted epithelial proliferation and the development of pro-acinar buds and ducts in regular homeostasis. In addition, EGCG’s antioxidant activity after IR injury effectively prevents epithelial cell apoptosis [ 107 ]. As a strong antioxidant, α-lipoic acid (ALA) is highly reactive to free radicals that can prevent normal tissue damage and dysfunction caused by radiation by increasing the level of glutathione in the tissues; this has been confirmed in the small intestine and thyroid of rats [ 108 , 109 ].…”
Section: Treatment Of Risgimentioning
confidence: 99%
“…SG pretreated with 7.5 µg/mL of EGCG promoted epithelial proliferation and the development of pro-acinar buds and ducts in regular homeostasis. In addition, EGCG’s antioxidant activity after IR injury effectively prevents epithelial cell apoptosis [ 107 ]. As a strong antioxidant, α-lipoic acid (ALA) is highly reactive to free radicals that can prevent normal tissue damage and dysfunction caused by radiation by increasing the level of glutathione in the tissues; this has been confirmed in the small intestine and thyroid of rats [ 108 , 109 ].…”
Section: Treatment Of Risgimentioning
confidence: 99%
“…Regular consumption of green tea may prevent cancer, diabetes, atherosclerosis, obesity, as well as bacterial and viral infections. Both in vitro and in vivo studies showed that green tea reduces the radiation-induced damage to cells and tissues ( 14 , 29 ). The present study revealed that the administration of EGCG prior to TBI preserved the crypt-villus architecture of the murine small intestine by promoting the survival of the Lgr5 + ISCs and the regeneration of the intestinal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Epigallocatechin gallate (EGCG) is the most abundant green tea polyphenol with numerous health benefits [ 79 , 80 , 81 , 82 ]. In colorectal carcinoma cells (HT-29), EGCG induced autophagy to inhibit the proliferation of cells through the regulation of the glycerophospholipid metabolic pathway [ 83 ].…”
Section: Roles Of Polyphenols In Autophagic Adaptation For Healthy Agingmentioning
confidence: 99%